A new species of Heterocondylus (Eupatorieae, Asteraceae) from Serra do Brigadeiro, Minas Gerais, Brazil - Lopes, Isabel T. F. V.; Marques, Danilo; Nakajima, Jimi N. (Phytotaxa, 2021)
The southeastern Brazilian phytophysiognomy of “campos de altitude” is threatened by the global temperature increase, and because of it, many of its endemic species, such as those of the Asteraceae family, may disappear over the next years. This new species, which occurs in this type of environment, belongs to the genus Heterocondylus (Eupatorieae: Asteraceae), which comprises seven species, mainly with South American distribution. This genus is morphologically variable but all its species share the diagnostic characters, such as: enlarged basal style with variable indumentum, and cypselae with an asymmetrical carpopodium composed of cells with thickened walls. Heterocondylus penninervius is described as a new species from the “campos de altitude” in Serra do Brigadeiro, Araponga municipality, Minas Gerais state, Brazil. The species is recognized by its sessile leaves concentrated in the lower part of the stem, with narrow-elliptical to narrow-lanceolate blade and penninerved leaves, as well as broad capitula with white and pinkish phyllaries. This study provides the description, illustration, taxonomic affinities, flowering and fruiting period and geographic distribution of the species.